Retrospective comparison of outcomes following tibial plateau levelling osteotomy and lateral fabello-tibial suture stabilisation of cranial cruciate ligament disease in small dogs with high tibial plateau angles. Issue 4 (4th July 2022) - Tikekar, A; De Vicente, F; McCormack, A; Thomson, D; Farrell, M; Carmichael, S; Chase, D
ABSTRACT: Aims: To compare short and long-term outcomes after tibial plateau levelling osteotomy (TPLO) and lateral fabello-tibial suture (LFTS) techniques for the management of cranial cruciate ligament disease in small dogs with high tibial plateau angles (TPA). Methods: In this retrospective study, the medical records of two veterinary specialist practices in the United Kingdom were searched for dogs (<20 kg) that underwent TPLO or LFTS between 2000 and 2010, and had a preoperative radiographic TPA >30° with either short-term (6 weeks) and/or long-term (>3 months) follow-up data. Data collected at a 6-week post-surgical re-examination was derived from orthopaedic examination and radiographic assessment and included the incidence of major and minor complications and scoring of the short-term outcome. Long-term outcome was scored based on results of a subjective owner questionnaire and veterinary orthopaedic examination. Results: A total of 61 (84 stifles) dogs were included in the study: 24 (30 stilfes) and 37 (54 stifles) dogs underwent LFTS and TPLO, respectively. Long-term clinical outcome was different (p = 0.017) between groups; 15/15 stifles in the TPLO group had a good or excellent long-term clinical outcome, compared to 4/8 (50%) in the LFTS group. There was no evidence of a difference in short-term post-operative outcome or owner subjective long-term outcome between treatment groups. Stifles in the LFTS group were more likely (p = 0.027) to have palpable stifle pain at long-term follow-up. Owners reported that 5/16 (31.3%) dogs in the LFTS group required oral non-steroidal anti-inflammatory drug (NSAID) treatment at least monthly (4/5 required daily treatment), whereas no dogs in the TPLO group required treatment with NSAID more frequently than three times per year (p = 0.011). No correlation was found between short-term outcome and owner subjective long-term outcome but there was a positive correlation between short-term outcome and long-term clinical outcome. There was no evidence of a difference in overall major complication rates between treatment groups. The occurrence of complications was associated with heavier body weight at the time of surgery. No other variables were shown to be risk factors for complications. Conclusion and clinical relevance: Small breed dogs with high TPA that underwent TPLO had better long-term clinical outcomes and were less likely to require NSAID administration than those that underwent LFTS. The risk of complication increased with the weight of the dog at surgery. There was a positive correlation between short-term outcome and long-term clinical outcome.